Protective effect of Astragaloside IV against sepsis-induced acute lung injury in rats - Ruiqin Huang; Min Li (Elsevier, 2016)
The study aimed to explore the protective effects of AS-IV against sepsis-induced ALI. Sepsis was induced by cecal ligation and puncture (CLP) method in Sprague Dawley rats. Rats were randomly assigned into five groups: animals undergoing a sham CLP (sham group); animals undergoing CLP (CLP group); animals undergoing CLP and treated with AS-IV at 2.5 mg/kg bw (low-dose AS-IV [L-AS] group), at 5 mg/kg bw (mid-dose AS-IV [M-AS] group), and at 10 mg/kg bw (high-dose AS-IV [H-AS] group). At 6 h, 12 h and 24 h post-CLP surgery, six rats were respectively sacrificed to collect blood and lung tissue samples. The levels of arterial blood gas index, lung water content, protein level and leukocyte counts (total amount, neutrophils and lymphocytes) in bronchoalveolar lavage fluid (BALF) and cytokines such as TNF-α and IL-6 in BALF were measured at each time point in different groups. HE-staining and optical microscopy were performed to examine the pathological changes in lungs. The 72 h-survival rate of each group was also recorded. PaO2 was decreased significantly, while the lung water content, BALF protein level, cell numbers, BALF cytokine TNF-α and IL-6 levels were increased significantly for CLP group as compared with sham group. Moreover, pathological injury was observed in lung tissue indicating the successful sepsis-induced ALI model. Speaking of the effect of AS-IV, we founded that, compared with the CLP group, the AS-IV treatment groups could significantly alleviate all the above negative changes exited in the CLP group in a dose-dependent manner. What's more, the pathological injury was also gradually improved by AS-IV treatment compared with the CLP rats. AS-IV exerts its protective effect against sepsis-induced ALI in rats via improving pulmonary ventilation function, decreasing the permeability of alveolar epithelium and capillary as well as repressing lung inflammation.